PENGARUH PEMBERIAN PUPUK KASCING DANHAYATI MIKORIZA TERHADAP SIFAT KIMIA TANAH DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) - Sumantri, Nadya Eka; Ardian, Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aimed to determine the effect of vermicompost and bio fertilizer mycorrhizal against chemical properties of soil and yield of sweet corn. Research conducted at the Experimental Farm Unit, Faculty of Agriculture, University of Riau soil type inceptisol and Soil Laboratory, Faculty of Agriculture, University of Riau from February to July 2016. The study was conducted experimentally using CRBD factorial with vermicompost fertilizer the first factor, namely 56.25 g/planting hole, 84.37 g/planting hole, 112.50 g/planting hole and the second factor was the biological mycorrhizal fertilizer 5 g/planting hole, 10 g/planting hole, and 15 g/planting hole so obtained 9 combination treatments and 3 replications. Data of soil chemical parameters were analyzed descriptively and data of crop yields statistically analyzed by analysis of variance was then tested further using Duncan's Multiple Range Test (DNMRT) 5%. The results showed that vermicompost fertilizer and mycorrhizal biological improved the chemistry of soil pH, organic C, total-N, P-total and CEC and affects the yield of sweet corn per plot.Keyword :sweet corn (Zea mays sacharata Sturt), vermicompost fertilizer, biological mycorrhizal, soil chemical properties